2006
DOI: 10.1002/jmri.20496
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative myocardial infarction on delayed enhancement MRI. Part I: Animal validation of an automated feature analysis and combined thresholding infarct sizing algorithm

Abstract: Purpose: To develop a computer algorithm to measure myocardial infarct size in gadolinium-enhanced magnetic resonance (MR) imaging and to validate this method using a canine histopathological reference. Materials and Methods:Delayed enhancement MR was performed in 11 dogs with myocardial infarction (MI) determined by triphenyltetrazolium chloride (TTC). Infarct size on in vivo and ex vivo images was measured by a computer algorithm based on automated feature analysis and combined thresholding (FACT). For compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
128
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 23 publications
2
128
1
3
Order By: Relevance
“…First, it could result merely from the volume-averaging effects of an area of uniformly fibrotic tissue (dense infarct scar) with an adjacent area of completely preserved, viable myocardium, particularly in situations in which spatial resolution is limited. 7,28,30 In this case, anatomically, there would be a single border between fibrotic scar and viable myocardium, and the limited spatial resolution would render an apparent intermediate SI in that border region. Certainly, partial volume effects because of this averaging effect of normal and necrotic tissue have been demonstrated by ceMRI in experimental animal studies 7,28,30 and are contributory.…”
Section: Partial Volume Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…First, it could result merely from the volume-averaging effects of an area of uniformly fibrotic tissue (dense infarct scar) with an adjacent area of completely preserved, viable myocardium, particularly in situations in which spatial resolution is limited. 7,28,30 In this case, anatomically, there would be a single border between fibrotic scar and viable myocardium, and the limited spatial resolution would render an apparent intermediate SI in that border region. Certainly, partial volume effects because of this averaging effect of normal and necrotic tissue have been demonstrated by ceMRI in experimental animal studies 7,28,30 and are contributory.…”
Section: Partial Volume Effectmentioning
confidence: 99%
“…7,28,30 In this case, anatomically, there would be a single border between fibrotic scar and viable myocardium, and the limited spatial resolution would render an apparent intermediate SI in that border region. Certainly, partial volume effects because of this averaging effect of normal and necrotic tissue have been demonstrated by ceMRI in experimental animal studies 7,28,30 and are contributory. However, a second possibility is that intermediate SI arises from the intermingling of discrete areas of preserved myocardium with bundles of fibrotic, infarcted scar within the same voxel.…”
Section: Partial Volume Effectmentioning
confidence: 99%
“…As it was shown that pathological assessment of infarct size can be better approximated by the use of the full width at half maximum criteria than simple intensity thresholding based on the standard deviation of normal myocardial signal intensities, we used this semiautomatic thresholding technique to measure infarct size. 25) After outlining the myocardial segment containing the region with high signal intensity, the maximum signal intensity region was determined. Scar was divided into an infarct core zone and a heterogeneous zone (ie, peri-infarct zone).…”
Section: Methodsmentioning
confidence: 99%
“…Infarct size was compared between single-shot, inversion-recovery (IR) true-FISP with motion-corrected averaging (eight averages) and conventional segmented IR turbo-FLASH using a previously validated semiautomatic computerized method (20,21) of objective measurement. Infarct size was measured on surface coil intensity-corrected PSIR images.…”
Section: Measurementsmentioning
confidence: 99%